Distribution of Harmful Algae (Karenia spp.) in October 2021 Off Southeast Hokkaido, Japan - Kuroda, Hiroshi; Taniuchi, Yukiko; Watanabe, Tsuyoshi; Azumaya, Tomonori; Hasegawa, Natsuki (Frontiers in Marine Science, 2022)
An unprecedented large-scale outbreak of harmful algae, including Karenia selliformis and Karenia mikimotoi, was reported in mid-September 2021 in the northwest Pacific Ocean off southeastern Hokkaido, Japan. It inflicted catastrophic damage on coastal fisheries in the ensuing months. To understand the spatiotemporal distribution of Karenia spp. abundance, we conducted extensive ship-based surveys across several water masses during 4–14 October, 2021 and analyzed in-situ data in combination with Sentinel-3-derived ocean color imagery with a horizontal resolution of 300 m. High chlorophyll-a concentrations (exceeding 10 mg m–3) were identified mainly in coastal shelf–slope waters of <1,000-m water depth occupied by Surface Coastal Oyashio Water or Modified Soya Warm Current Water. Karenia spp. abundance was strongly correlated with chlorophyll-a concentration, which typically had a shallow vertical maximum within the surface mixed layer. Large- and small-scale distributions of Karenia spp. abundance at the ocean surface were estimated from two satellite-imagery products: maximum line height and red-band difference. Maps generated of Karenia spp. abundance revealed snapshots of dynamic Karenia bloom distributions. Specifically, the cores of Karenia blooms were located on continental shelves, sometimes locally exceeded 104 cells mL–1, and seemed to be connected intermittently to very nearshore waters. Relatively high-abundance areas (>103 cells mL–1) of Karenia spp. on the shelf were characterized by submesoscale (i.e., 1–10 km) patch- or streak-like distributions, or both. Within a roughly 24-h period from 12 to 13 October, Karenia-spp. abundances averaged over the shelf abruptly increased more than doubled; these abundance spikes were associated with the combined effects of physical advection and algal growth. The obtained maps and features of Karenia spp. abundance will provide basic estimates needed to understand the processes and mechanisms by which algal blooms can inflict damage on regional fisheries.